Born to be Alive: A Role for the BCL-2 Family in Melanoma Tumor Cell Survival, Apoptosis, and Treatment - Anvekar, Rina A.; Asciolla, James J.; Missert, Derek J.; Chipuk, Jerry E. (Frontiers in Oncology, 2011)
The global incidence of melanoma has dramatically increased during the recent decades, yet the advancement of primary and adjuvant therapies has not kept a similar pace. The development of melanoma is often centered on cellular signaling that hyper-activates survival pathways, while inducing a concomitant blockade to cell death. Aberrations in cell death signaling not only promote tumor survival and enhanced metastatic potential, but also create resistance to anti-tumor strategies. Chemotherapeutic agents target melanoma tumor cells by inducing a form of cell death called apoptosis, which is governed by the BCL-2 family of proteins. The BCL-2 family is comprised of anti-apoptotic proteins (e.g., BCL-2, BCL-xL, and MCL-1) and pro-apoptotic proteins (e.g., BAK, BAX, and BIM), and their coordinated regulation and function are essential for optimal responses to chemotherapeutics. Here we will discuss what is currently known about the mechanisms of BCL-2 family function with a focus on the signaling pathways that maintain melanoma tumor cell survival. Importantly, we will critically evaluate the literature regarding how chemotherapeutic strategies directly impact on BCL-2 family function and offer several suggestions for future regimens to target melanoma and enhance patient survival.